2023
DOI: 10.1128/spectrum.00681-23
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody targeting spore wall protein 1 inhibits the proliferation of Nosema bombycis in Bombyx mori

Bin Yu,
Rong Zheng,
Maofei Bian
et al.

Abstract: Microsporidia are obligate intracellular single-cell eukaryotic parasites that can infect almost all kinds of animals and cause microsporidiosis. However, there are a few achievements of microsporidiosis treatments. Nosema bombycis could cause a microsporidiosis condition, pébrine, in the silkworm. Treatment and prevention of pébrine are still the research hotspots in sericulture. In this study, N. bombycis was treated with K 2 CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The copyright holder for this preprint this version posted June 27, 2024. ; https://doi.org/10.1101/2024.06.27.600942 doi: bioRxiv preprint silkworms from infection with N. bombycis. Previous studies have shown that the transgenic expression of monoclonal antibody single-chain variable fragments (scFvs) targeting N. bombycis protein in silkworm or host cell lines reduced N. bombycis infection and proliferation [56][57][58]. As host cell apoptosis promotes the clearing of infected cells and reduces the load of N. bombycis, we can express monoclonal antibody scFv against NbSPN14 in silkworm to block the N. bombycis serpin inhibiting host cell apoptosis; as a result, the resistance of the host silkworm to N. bombycis will enhance.…”
Section: Microsporidia Including E Cuniculi Vittaforma Corneae Nosema...mentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 27, 2024. ; https://doi.org/10.1101/2024.06.27.600942 doi: bioRxiv preprint silkworms from infection with N. bombycis. Previous studies have shown that the transgenic expression of monoclonal antibody single-chain variable fragments (scFvs) targeting N. bombycis protein in silkworm or host cell lines reduced N. bombycis infection and proliferation [56][57][58]. As host cell apoptosis promotes the clearing of infected cells and reduces the load of N. bombycis, we can express monoclonal antibody scFv against NbSPN14 in silkworm to block the N. bombycis serpin inhibiting host cell apoptosis; as a result, the resistance of the host silkworm to N. bombycis will enhance.…”
Section: Microsporidia Including E Cuniculi Vittaforma Corneae Nosema...mentioning
confidence: 99%